1998
DOI: 10.1159/000023175
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glucagon-Like Peptide 1 (7–36 Amide) on Glucose Kinetics during Somatostatin-Induced Suppression of Insulin Secretion in Healthy Men

Abstract: Glucagon-like peptide 1 (GLP-1) is known to stimulate insulin secretion and biosynthesis, but has also been shown to decrease insulin requirements in type 1 diabetic subjects suggesting insulin-independent effects. To assess whether GLP-1 exerts also direct effects on whole-body glucose metabolism, 6,6-D2-glucose kinetics were measured in 8 healthy volunteers receiving once GLP-1, once saline during hyperglycemic glucose clamping, while somatostatin with replacement amounts of insulin, glucagon and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…This suggests that maximal insulin suppression during the oGTT was achieved by the direct octreotide effect alone, which is in accordance with the reported insulin suppression by even lower octreotide doses than ours (17,23). However, GLP-1 has additional effects, including glucagon suppression, stimulation of pancreatic somatostatin release (8,11,24) and possibly a peripheral effect on glucose uptake/insulin sensitivity (13), although the latter remains controversial (12,14). While a mouse model with disrupted GLP-1 receptor signaling (25) suggests that only its incretin effect is essential for glucose homeostasis, disruption of other GLP-1 actions may still be important for the fine tuning of the metabolic response to oral nutrients.…”
Section: European Journal Of Endocrinology (1999) 140supporting
confidence: 85%
See 1 more Smart Citation
“…This suggests that maximal insulin suppression during the oGTT was achieved by the direct octreotide effect alone, which is in accordance with the reported insulin suppression by even lower octreotide doses than ours (17,23). However, GLP-1 has additional effects, including glucagon suppression, stimulation of pancreatic somatostatin release (8,11,24) and possibly a peripheral effect on glucose uptake/insulin sensitivity (13), although the latter remains controversial (12,14). While a mouse model with disrupted GLP-1 receptor signaling (25) suggests that only its incretin effect is essential for glucose homeostasis, disruption of other GLP-1 actions may still be important for the fine tuning of the metabolic response to oral nutrients.…”
Section: European Journal Of Endocrinology (1999) 140supporting
confidence: 85%
“…These include glucagon suppression and slowing of gastric motility (8,11). A peripheral effect on glucose uptake and metabolism is controversial (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of these in vivo extrapancreatic effects of GLP-1, when intravenously administered, has been suggested in man, normal and diabetic (Gutniak et al 1992, D'Alessio et al 1994, Shalev et al 1998, and also in depancreatized dogs (Sandhu et al 1999) and diabetic rats (Mizuno et al 1997), but its relevance is questioned by other studies on healthy humans (Toft-Nielson et al 1996, Orskov et al 1996, Ryan et al 1998, type 2 diabetic patients , Vella et al 2000 and insulin-dependent diabetic dogs (Freyse et al 1999). Still, a recent work (Vella et al 2001) performed in type 1 diabetic subjects has demonstrated that in the presence of hyperglycemia, hyperinsulinemia and enterally delivered glucose, GLP-1 does not modify splanchnic but increases total body glucose uptake, the skeletal muscle being, most probably, responsible for it.…”
Section: Discussionmentioning
confidence: 96%
“…Subsequently, several groups noted effects of GLP-1 to promote glucose uptake in skeletal muscle, adipocyte, or hepatocyte preparations in vitro (16,21,27,45). Although the initial in vivo study by Gutniak et al was consistent with the in vitro results, subsequent studies in humans have been divergent, with some studies favoring extrapancreatic effects of 12,15,29,30,39,43) and others showing no effect (2,34,38,44). Furthermore, even among the studies that demonstrated an extrapancreatic effect, there has been a disparity in the apparent site of action of the GLP-1, with some investigators suggesting an effect on peripheral tissues (15,29,30,43), whereas others suggested an effect on endogenous glucose production (EGP; see Ref.…”
mentioning
confidence: 78%